EVALUASI KEBIJAKAN KARTU JAKARTA PINTAR TINGKAT SMA/SMK NEGERI DI JAKARTA SELATAN (Periode Tahun Ajaran 2013-2014) - Nadia Fakhrunnisa Suripto; Puji Astuti; Lusia Astrika (Journal of Politic and Government Studies, 2015)
As seen by level of poverty case that has been related to dropout number in DKI Jakarta, accordingly local government of DKI Jakarta on December 2012 has released their new program called by Kartu Jakarta Pintar which is one of Personal Education Funding Aid. With this policies, the the Government of Jakarta give an access for those who can not get their education at least until Senior High School or Vocational School as DKI Jakarta citizen. The aid is fully supported by the national income of DKI Jakarta. Principally, the aim of Kartu Jakarta Pintar’s program is considered as an effort to increase the society especially students who comes from needy family to complete 12 years compulsory education in DKI Jakarta.The purpose of this research aim is to find out implementation of KJP policies in the High School and Vocational School level especially in Southern Jakarta in 2013-2014 and also to find out the obstacle and proponent factors from this policy The type of this research is descriptive research. Method of this research is qualitative and data collecting technique use interview and document analysis.The evaluation result of policies shows that: KJP policy for Senior High School and Vocational School in period 2013-2014 have not succeeded yet. In 2013-2014 this program is considered not success. Due to it was found much discrepancy between normative goal and empiric situation in society. The discrepancy happened because of obstacle in implementation of KJP. The factors that become an obstacle in KJP Program in Southern Jakarta for example : (1)the lack of human resource and financial to support KJP Program for period 2013-2014, (2) the selection process of KJP receiver base on SKTM involved some of student misunderstanding as incompetent receiver even though they already had SKTM, (3) the distribution of KJP funding in 2013-2014 sustained a delay due to there were many school still propose KJP program out of the school record and it2caused double account problems, (4) lack of observation for this program either from the school or Education Service.The writer recommend are: (1) The role of observer institute should be improve to monitor and evaluate KJP Program either from Education Service, School or even the society to minimize the distortion of this program, (2) the government needs to increase budget for KJP Program due to the necessity of education will be increase from time to time, (3) the school should be make direct observe (home visit) in order to process the data collection of KJP receiver.Key words: Policy, Evaluation, Kartu Jakarta Pintar (KJP)PENDAHULUAN